O papel das redes de transformação no processo de inovação: estudos de caso sobre a descoberta e a comercialização da inovação - Vitoreli, Marinez Cristina [UNESP] (2013)
Innovation is widely recognized as important. In addition, in this context, innovation networks have gained importance in academic studies, since an organization alone, does not always have access to all necessary resources. Gobbo Junior and Olsson (2010) proposed a model of network innovation whereby the transformation networks would be the linking structures between exploration and exploitation networks. In this context, this paper presents two case studies of innovation networks, aiming to increase the understanding on transformation networks. The objective was to understand how they interconnect exploration and exploitation networks; the main actors present in this interface; and to evaluate whether these actors can act as agents, to accelerate the innovation process. It was possible to verify how the transformation networks interconnect exploration and exploitation, and identify the practices and their main actors.